2016
DOI: 10.1186/s12889-016-3262-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing child abuse amongst adolescents in low- and middle-income countries: A pre-post trial in South Africa

Abstract: BackgroundNo known studies have tested the effectiveness of child abuse prevention programmes for adolescents in low- or middle-income countries. ‘Parenting for Lifelong Health’ (http://tiny.cc/whoPLH) is a collaborative project to develop and rigorously test abuse-prevention parenting programmes for free use in low-resource contexts. Research aims of this first pre-post trial in South Africa were: i) to identify indicative effects of the programme on child abuse and related outcomes; ii) to investigate progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 38 publications
1
54
0
3
Order By: Relevance
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents one study which used a pre-post non-randomised design. Sinovuyo Caring Families in South Africa is distinct from other parenting programmes described, as it targets older children who have been identified as having behavioural problems or a suspected history of abuse (Cluver, Lachman et al 2016;Cluver, Meinck et al 2016). Designed specifically to address CM, it also reported outcomes for IPV, both measured quantitatively.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tirere Pamwe program is built on the integration of life course development research, community epidemiology, and preventive intervention (Schiavo, ; Trickett et al, ). Child maltreatment is a pressing problem that co‐occurs in individuals and neighbourhoods (L. Cluver, Meinck et al., ; Ravi & Ahluwalia, ), and can sometimes be predicted by common precursors, and prevented through protective factors that mediate or moderate exposure to risky situations (Dawes & Ward, ; Finkelhor, Turner, Ormrod, & Hamby, ; Masinda & Muhesi, ). There is much overlap in these risk and protective factors.…”
Section: Tirere Pamwe Parent Training Programmentioning
confidence: 99%